Novel Synthesis of a New Surfactant 4‐((4‐Bromophenyl)(dodecyl)amino)‐4‐Oxobutanoic Acid Containing a Benzene Ring Using a Copper Catalyst Cross‐Coupling Reaction and its Properties. Issue 4 (15th December 2012) - Chen, Minggui; Hu, Xinqi; Fu, Meilong
Abstract: A new surfactant 4‐((4‐bromophenyl)(dodecyl)amino)‐4‐oxobutanoic acid with a benzene spacer was synthesized via a novel copper catalyzed cross‐coupling reaction. Its structure was confirmed by FTIR, 1 H‐NMR, 13 C‐NMR and HRMS; its purity was checked by HPLC. Dynamic light scattering and an atomic force microscope showed that it forms an unusual large‐diameter premicellar aggregation below the CMC.